Comparative assessment of relationship between sensation seeking with job stress in emergency medicine workers and non emergency medicine workers - M Mahboubi; A Jalali; M Mohammadi (Tehran University of Medical Sciences, 2013)
Abstract Background: Job environment is a strong stimulus for created of emotions and there are several stressful situations which could causes dissatisfaction, low work performance, quit or job-changing. The purpose of this study is to determine the relationship between sensation seeking with job stress among emergency medicine workers and non emergency medicine workers. Methods: In this cross-sectional study, 60 emergency medicine workers chosen the census method and 60 non emergency medicine workers chosen the convenience sampling method, in border cities of KUMS, were selected for study. Data were collected by valid and reliable questionnaires of job stress and sensation seeking. Data were analyzed using descriptive and analytical statistics. Results: The most rate of job stress among emergency medicine workers was in the level of moderate (46.6percent) and in the non-emergency medicine workers was the low level (56.4percent) and the most rate of sensation seeking among emergency medicine workers was in the level of lower the moderate (35 percent) and in the non-emergency medicine workers was lower the moderate level (40 percent). There were indirect relationship between job stresses with to be thrilled, to be experienced and to be diversity of the variable of sensation seeking and there was a direct relationship between to be blues and to be scope of inhibition of the variable of sensation seeking. Conclusion: Results can be regarded managers to decrease of losses due to job stress and increase productivity, especially in emergency medicine workers across the country